Dual Polarization Microstrip Array Antenna For WLAN Application - Mohd Syaiful Redzwan , Mohd Shah (2011)
The advantages of microstrip antennas have made them a perfect candidate for use in the Wireless local area network (WLAN) applications. Though bound by certain disadvantages, microstrip patch antennas can be tailored so they can be used in the new high-speed broadband WLAN systems. The design and development of a dual linearly polarized microstrip antenna operating at center frequency of 2.4 GHz is presented in this thesis by using one port with single layer. This design presents an array antenna from type of inset-fed microstrip patch antenna oriented at 45° and -45°. The antenna is capable to generate dual-polarization radiation pattern slanted at 45° and -45°. Combinations of two and more patches using quarter-wave impedance matching technique have been used to design the array antenna. The design were simulated using CST Studio Suite 2008 and were fabricated on FR4 substrate with a dielectric constant Er = 4.7, tan () = 0.019 and thickness =1.6mm. Then, the fabricated antenna were measured by using network analyzer. The measurement show, the dual polarization microstip array antennas demonstrate larger bandwidth and increase the gain response compared to the single antenna. It provides an impedance bandwidth of 5% (from 2.412 to 2.484GHz) below lOdB and the gain of antenna achieve about 5.01 dBi, so that it easily covers the required universal 2.4GHz bandwidths for wireless local area network applications (WLAN).